Study of the influence of the effects of antihypertensive therapy on the functional state of the BP regulation system in patients with essential hypertension stage II and a normal body mass index - Palamarchuk, O. I.; Fushtey, I. M.; Podsevahina, S. L.; Паламарчук, Олександр Іванович; Фуштей, Іван Михайлович; Подсевахіна, Світлана Леонтіївна (My University, 2024)
The goal of the present study was to investigate the effects of combination of angiotensin-converting enzyme (ACE) inhibitors and a selective imidazoline receptor agonist on the functional state of the blood pressure regulation system in male patients with essential hypertension (EH) stage II with a normal body mass index.
Keywords: тези доповідей